DEVELOPMENT OF NUMERACY LITERACY INSTRUMENTS TO IMPROVE HIGH-LEVEL THINKING SKILLS IN JUNIOR HIGH SCHOOL STUDENTS - Hidayatullah, Arif; Nindiasari, Hepsi; Sukirwan, Sukirwan (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
The background to this research is that there are very few numeracy literacy questions, students are still not trained enough to work on numeracy literacy questions, and teachers are not optimal in understanding the development of numeracy literacy questions even though in an effort to improve HOTS abilities students need to get used to dealing with numeracy literacy questions. This study aims to develop a math HOTS measuring instrument for first semester VII graders of junior high school (SMP) students. The research method is research and development with ADDIE stages namely analysis, design, development, implementation, and evaluation. The instruments used in the research were numeracy literacy test questions in the form of descriptions, observation sheets, response questionnaires, and interview sheets. The research flow begins with the initial analysis, the development of a grid of numeracy literacy questions, expert validation, revision, practitioner testing, small-scale trials, revisions, and large-scale trials. The results of the study were 18 items of numeracy literacy with Competency Standards for Numbers, Sets, Algebra, and Systems of Two-Variable Linear Equations. The numeracy literacy instrument indicators developed include analytical, evaluation, and creative abilities. The questions developed have valid quality as seen from the validity test of all the items above 0.5, reliability 0.86, difficult and moderate difficulty levels, and good and sufficient discriminating power. The mean HOTS score of students was 71. The conclusion of this study was to produce a valid and reliable HOTS measuring numeracy literacy instrument for junior high school students.